"SUBVERSIVE SOMATOLOGY": EMBODIED COMMUNICATION IN THE EARLY MODERN STAG HUNT. (1st June 2019) - Lambert, Shannon
Using the performative and affective elements of Gilles Deleuze's conception of "meat, " I argue that the literary representation of stag hunting in the early modern period can serve as a model for an embodied understanding of interspecies communication and interaction. The stag hunt—more than any other form of hunting during the early modern period—is frequently construed in allegorical terms, which sustain human-animal divisions and reinforce notions of human superiority. However, beginning with George Gascoigne's treatise The Noble Arte of Venerie or Hunting (1575), I explore how elements of the stag hunt like imitation blur these boundaries, posing a challenge to essentialist conceptions of the human, and opening up more fluid mediums of corporeal communication.I then turn to Jaques' encounter with the stag in Shakespeare's As You Like It (1599) to consider the potential for trans-species communication of material "passions." My approach resonates with current work like that of Ralph Acampora, which attempts to shift the grounds of humans' ethical consideration for animals from the psyche to the soma.